Collaboration with middle leaders and teachers leadership emphasis of compulsory school principals in Iceland - Hansen, Börkur; Lárusdóttir, Steinunn Helga (Menntavísindasvið Háskóla Íslands, 2020)
Current theories on school leadership focus on principals’ vision of their role and their relations with school personnel. More specifically, school leadership is now viewed as a collaborative effort between principals and teachers in providing leadership in the area of teaching and learning (Harris, 2008; Kaplan & Owings, 2015; Louis, Leithwood, Wahlstrom & Anderson, 2010; Robinson, 2011; Sergiovanni, 2009). The main objective of this emphasis on collaboration is to contribute to improved educational quality in schools (Hoy & Miskel, 2008; Sergiovanni, 2009; Woolfolk-Hoy & Hoy, 2009). This paper reports on a study of the leadership emphasis compulsory school principals in Iceland place on collaboration with middle leaders and teachers. The focus is on two forms of collaborative leadership, prominent in the 21st century, distributed leadership and teacher leadership.The study was conducted in 2017. Data was gathered with an electronic questionnaire sent to all Icelandic compulsory school principals, 162 individuals, in the spring of 2017. The number of respondents was 111, making the response rate 69%. The questionnaire was designed and administered by means of the Qualtrics software system and data analysis was conducted using the SPSS and EXCEL programs. The principals were asked to estimate, on a five point Likert scale, the time they devote to working with middle leaders, teachers, and other school staff. They were also asked to estimate their emphasis on involving middle leaders in decision-making on significant issues in their schools. Furthermore, they were asked to estimate their emphasis on middle leaders and teachers providing leadership concerning the development of teaching and learning.The following background information was used for analysing the data: background variables concerning the principals’ age, gender, education, experience as principal, experience as assistant principal; background variables concerning circumstances within the schools, such as their size (number of ...